Dead time influence on operating modes of transistor resonant inverter with pulse frequency modulation (PFM) - Antchev, Mihail hristov; Antchev, Hristo mihailov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This study explores the impact of dead-time on the transistor resonant inverter operating modes depending on the ratio of the transistor switching frequency and the resonant frequency of the series-resonance circuit in the diagonal of the transistor bridge. On the basis of theoretical data and experimental results, a dead-time limitation relation has been offered - besides for a minimum value but for a maximum value. This provides extension of the operating mode range in zero voltage switching (ZVS).